2019
DOI: 10.3174/ajnr.a6033
|View full text |Cite
|
Sign up to set email alerts
|

Increased Water Content in Periventricular Caps in Patients without Acute Hydrocephalus

Abstract: BACKGROUND AND PURPOSE: Periventricular caps are a common finding on MR imaging and are believed to reflect focally increased interstitial water content due to dysfunctional transependymal transportation rather than ischemic-gliotic changes. We compared the quantitative water content of periventricular caps and microvascular white matter lesions, hypothesizing that periventricular caps associated with increased interstitial fluid content display higher water content than white matter lesions and are therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…WMH in this region has characteristic histology of spongiotic, finely textured myelin and accumulation of interstitial fluid within the adjacent white matter and sub-ependymal widening of the extracellular space around the lateral ventricle horns. 48 quantitative MRI study measuring brain water content identified the periventricular caps as having significantly higher water content compared to normal white matter, 47 further supporting our periventricular WMH pattern as a distinct white matter region. Similarly, we also identified a posterior WMH pattern associated with age but not with any disease risk factor or cognitive impairment.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…WMH in this region has characteristic histology of spongiotic, finely textured myelin and accumulation of interstitial fluid within the adjacent white matter and sub-ependymal widening of the extracellular space around the lateral ventricle horns. 48 quantitative MRI study measuring brain water content identified the periventricular caps as having significantly higher water content compared to normal white matter, 47 further supporting our periventricular WMH pattern as a distinct white matter region. Similarly, we also identified a posterior WMH pattern associated with age but not with any disease risk factor or cognitive impairment.…”
Section: Discussionsupporting
confidence: 78%
“…44 It is interesting that our proposed AD-related WMH location involving the parietal subcortical white matter overlap with the stereotypical temporoparietal cortical pattern 45 of amyloid pathology in AD and supports the suggestion that white matter tracts originating from neurons affected by Aβ deposition in the overlying cortex may be vulnerable to Wallerian degeneration-associated axonal damage triggered by the cortical AD pathology. 44 An interesting finding was the delineation of periventricular WMH pattern as periventricular caps around the frontal and posterior horns of the lateral ventricles with a thin lining along the lateral ventricles, 46 which was not associated with any disease risk factors examined or cognitive impairment. The periventricular cap pattern of WMH is a common finding on cranial MRI in the older participants, 46 postulated to be distinct from CSVD-related WMH and related to normal aging, 47 consistent with our observation of a singular association with age.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…T2 mapping is based on the acquisition of T2-weighted Turbo/Fast Spin Echo (FSE) or Gradient-Echo (GE) sequences with different TEs to assess the decay of T2 signal intensity. This approach is more precise than visual estimation of NEPSA with conventional T2-WI sequences [91]. Another valid approach to evaluate T2 relaxation times is based on synthetic MRI multi-echo quantitative scans that provide information about proton density, longitudinal relaxation rate (R 1 ) and transverse relaxation rate (R 2 ) [92].…”
Section: T2 Mappingmentioning
confidence: 99%
“…In iNPH, DTI was used to evaluate changes in white matter tracts and found increased fractional anistropy (FA), reduced mean diffusivity and increased oriental coherence in the corticospinal tract 6 , 7 or decreased FA in the corpus callosum and increased FA in the internal capsule 8 as reviewed by Siasios and colleagues 9 . In a recent study using a quantitative multi-echo, gradient-echo water mapping sequence in a cohort of patients with neurovascular symptoms an increased water content in periventricular caps compared to DWMH was described 10 . Though to date, focused evaluation of iNPH-associated T2w hyperintense white matter changes based on current diffusion sequences is missing.…”
Section: Introductionmentioning
confidence: 99%